Solid stress compression enhances breast cancer cell migration through the upregulation of Interleukin-6 - Azizan, Farouq; Sheriff, Ryna Shireen; Goh, Corinna Jie Hui; Chiam, Keng Hwee; Koh, Cheng-Gee (Frontiers in Cell and Developmental Biology, 2025)
Apart from biochemical signals, tumour cells respond to biophysical and mechanical cues from their environment. The mechanical forces from the tumour microenvironment could be in the form of shear stress, tension, or solid stress compression. In this study, we explore the effects of solid stress compression on tumour cells. Solid stress compression, a prevalent biomechanical stimulus accumulated during tumour growth, has been shown to enhance invasive and metastatic phenotypes in cancer cells. However, the underlying molecular mechanism that elicits this aggressive metastatic phenotype, especially in breast cancer, is not extensively studied. Using an established 2D in vitro setup to apply incremental solid stress compression, we found that migratory and invasive capacities of aggressive breast cancer cells were enhanced in a biphasic manner. We also found that the transcript and protein levels of Interleukin-6 (IL-6) and SNAI1 were upregulated in response to solid stress. The resultant increased secretion of IL-6 could in turn lead to autocrine activation of downstream signalling pathways and impact on cancer cell migration and invasion.